1124 Assessing changes in the upper airway using 3-dimensional segmentation after craniofacial distraction surgery in children with syndromic craniofacial anomalies. (17th August 2022) - Loo, Lucas; Smith, Luke; Ong, Juling
Abstract : Aims: Craniofacial deformities are associated with functional morbidities, such as airway obstruction. 1 Primary management involves fronto-facial distraction surgery, intending to normalise facial appearance as well as treating cephalocranial disproportion, exorbitism, and anatomical airway compromise. 2 This study aims to demonstrate, by using 3-Dimensional (3D) segmentation technology, the significant airway differences which result from fronto-facial distraction in paediatric patients with syndromic craniosynostosis. It further aims to illustrate that this methodology allows more variables to be analysed when compared with current conventional methods, such as computerised tomography (CT). Methods: 24 paediatric patients with syndromic craniosynostosis who underwent fronto-facial surgery between 2015 to 2021 at Great Ormond Street Hospital were included in the study. Pre- and post-op CT scans were analysed using Materialise Mimics 3D software to produce 3D software models of the upper airway ( figure 1 ). Non-mobile skeletal landmarks were registered both on pre-and post-op CT scans to enable accurate comparison of airway changes between the two time points. 3D phantoms were generated by isolating areas with air on CT scans (-1024 to -199 Hounsfield units). Materialise 3-Matic 3D software was used to analyse airway variables: volume (total pharyngeal, nasopharynx, and oropharynx), surface area, cross-sectional area, sphericity, and proportion of airway constrictions (constricted airway was defined as areas where airway diameter was less than 4 millimetres). Results: Raw data was transformed to reflect relative changes in variables versus absolute change. This was to account for age and clinical presentation variances in the study population. Significant increases were measured in total pharyngeal (76% mean increase), nasopharyngeal (277% mean increase), and oropharyngeal (54% mean increase) volume following fronto-facial surgery. Surface area (58.57% mean increase) and cross-sectional area (21.57% mean increase) of airway increased. There was a modest increase in airway patency (5.74% mean increase). Sphericity was slightly decreased (-3.33% mean decrease). However, the differences in sphericity and proportion of airway constriction were not significant. Conclusion: 3D technology can demonstrate the complex changes that result from fronto-facial surgery in children with syndromic craniosynostosis. It provides clinicians with additional avenues to assess a multitude of objective changes that come with treatment and recovery. There is also potential for using this technology to enrich the training of doctors and students. Although there is some evidence that surgery improves functional aspects of airway physiology, further work is needed to elicit precise variables that contribute to clinical outcomes. References: Hemifacial microsomia: clinical features and pictographic representations of the OMENS classification system, GOUGOUTAS, A. J., SINGH, D. J., LOW, D. W. & BARTLETT, S. P. 2007. Linear and Volumetric Airway Changes After Maxillomandibular Advancement for Obstructive Sleep Apnea, BUTTERFIELD, K. J., MARKS, P. L. G., MCLEAN, L. & NEWTON, J. 2015.